Preparing preservice teachers to be data literate: a Queensland case study. Issue 3 (27th May 2018) - Carey, Michael; Grainger, Peter; Christie, Michael
ABSTRACT: Data driven pedagogy has been introduced into Australian schools over the last decade to improve student learning outcomes, but are teacher educators preparing preservice teachers to be data literate? We used a survey to investigate ready-to-graduate preservice teachers' beliefs regarding their knowledge and skills in data literacy. Before entering a course on data literacy their belief responses indicated that they had basic data interpretation knowledge, but they were unsure of how to translate that knowledge into the classroom to improve student outcomes. The survey was administered again after a data literacy course, which included a five-week supervised professional experience task of observing data being used in schools to drive pedagogy. The post-course survey responses showed students increased confidence in their ability to interpret and use data, suggesting that a data literacy course linked to the professional experience task improves teachers' sense of preparedness to use data in the classroom. Keywords: Data literacy; professional learning.